Bioinorganic Chemistry : Inorganic Elements in the Chemistry of Life - Kaim, Wolfgang; Klein, Axel; Schwederski, Brigitte (West Sessex: Wiley, 2013)
Bioinorganic Chemistry: Inorganic Elements in the Chemistry of Life, Second Edition provides a detailed introduction to the role of inorganic elements in biology, taking a systematic element-by-element approach to the topic. The second edition of this classic text has been fully revised and updated to include new structure information, emerging developments in the field, and an increased focus on medical applications of inorganic compounds. New topics have been added including materials aspects of bioinorganic chemistry, elemental cycles, bioorganometallic chemistry, medical imaging and therapeutic advances.
Keywords: Biological functions; Chemotherapy involving nonessential elements; Iron-sulfur